2016
DOI: 10.17814/mechanik.2016.5-6.71
|View full text |Cite
|
Sign up to set email alerts
|

Slide and ball finishing burnishing of aluminium alloy surface after milling

Abstract: Główną cechą jakości technologicznej części maszyn jest ich odporność na zużywanie się, determinowana właściwo-ściami ich warstwy wierzchniej (WW). Jedną z wielu właści-wości WW wpływających w sposób istotny na odporność na zużywanie się współpracujących części maszyn jest określana za pomocą profilometru struktura geometryczna powierzchni (SGP), w tym m.in. parametry wysokościowe chropowatości powierzchni (zwykle im mniejsze tym lepiej) i udział materiałowy profilu chropowatości (lepszy większy).Obróbka nagni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Moreover, comparing the test results obtained for orthogonal rolling and sliding burnishing, the researchers concluded that rolling burnishing yields lower a R values and higher a KR values [55]. At present, machining of superalloys is becoming more and more important.…”
Section: Analysis Of the Effect On The Wear Of Austenitic Ductile Cas...mentioning
confidence: 98%
See 3 more Smart Citations
“…Moreover, comparing the test results obtained for orthogonal rolling and sliding burnishing, the researchers concluded that rolling burnishing yields lower a R values and higher a KR values [55]. At present, machining of superalloys is becoming more and more important.…”
Section: Analysis Of the Effect On The Wear Of Austenitic Ductile Cas...mentioning
confidence: 98%
“…The relevant SL properties of machine parts are most often achieved in mechanical treatment processes, often preceded by heat or thermal and chemical treatment. The wear resistance of mating machine parts is significantly affected by the roughness of their surfaces and SL hardness [55].…”
Section: Analysis Of the Effect On The Wear Of Austenitic Ductile Cas...mentioning
confidence: 99%
See 2 more Smart Citations